Formation and development of lamellar histoarchitecture of the ventricular myocardium of chick embryos - Bumeister, V.I.; Dudok, O.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. The existence of several models of the myolamellar structure of the ventricular myocardium, which currently has a number of contradictory provisions, reflects the need for a reasonable integration of the results of different methods. Under these circumstances, the study of those ontogenetic mechanisms that are responsible for the formation and development of the myolamellar architecture of the myocardium is of great interest. The purpose of the study is to determine the ontogenetic transformations of the embryonic chicken heart that ensure the formation and development of the myolamellar structure of the ventricular myocardium. Methods. The work examined the embryos of Cobb500 cross chickens from the beginning of the 10th day to the 21st day of incubation. The lamellar organization of the ventricular myocardium was studied using light and transmission electron microscopy. Results. Starting from the 36th stage according to NN (the beginning of the 10th day of incubation), the active development of the stromal component was observed in the heart of chicken embryos, which led to the division of the tissue of the compact ventricular myocardium into groups of muscle fibers in the form of narrow elongated flat plates containing thicker than 3 to 5 rows of cardiomyocytes. At the 41st and 43rd stages of development, active development of the intercellular matrix and division of the myocardium mass into muscle plates continued as part of the compact ventricular myocardium. The intercellular spaces within the plates narrowed, and between the myolamellae, the perimysium accumulated elements of the microcirculatory bed, functionally active fibroblasts, a large amount of amorphous substance, and bundles of formed collagen fibers. At the final stages of embryogenesis, the muscle plates of the left ventricle acquired a pronounced spiral orientation with a gradual displacement of the long axis of the muscle fibers in the direction from the apex of the ventricle to its base. In the wall of the right ventricle, the location of the myolamella acquired a transverse oblique-circular orientation. Conclusion. A comparison of the structure and geometry of the myolamella made it possible to reveal that starting from the 38th stage of development in the left ventricle, the conditions for the translational-rotational mechanism of chamber contraction were formed and increased, in which the formation of the difference between the systolic and diastolic volumes of the left ventricle is ensured not only by the longitudinal apico-basal vector compression of the cavity, but also by mutual sliding of spirally oriented plates in the ventricular wall. In right ventricle, the contraction mechanism is based on the longitudinal-circular compression of the chamber in accordance with the oblique-circular orientation of the muscle fibers in the composition of the myolamella without displacement in the state of systole.